Relationship Between Gestation Length and Birth Weight in Nigerian Sheep and Their Crosses - Iyiola-Tunji, AO; Akpa, GN; Nwagu, BI; Adeyinka, IA; Osuhor, CU; Lawal, TT; Ojo, OA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Effect of genotype and birth weight on gestation length was evaluated using Nigerian breeds of sheep and their crosses. The study was carried out at the Sheep Project Unit of Small Ruminant Research Programme (SRRP) of National Animal Production Research Institute (NAPRI), Ahmadu Bello University, Shika-Zaria. The sheep breeds used were Balami, Uda and Yankasa. Heat (estrus) detection was carried out twice daily; in the morning (07:00-08:00 hours); and in the evening (16:00-17:00 hours) using apron fitted rams to pick does on heat. A total of 56 lambs were used for this study. The data obtained were subjected to analysis of variance using General Linear Model and Correlation Procedure of SAS. All the genotypes had similar gestation length with values between 150.3±0.61 days and 153.3±0.60 days, except for Balami pure breed (BAL X BAL) lambs that recorded a shorter gestation length (137.1±0.81 days). There was a wide variation in the birth weight of lambs with the crosses between Balami rams and Yankasa ewes recording a distinct birth weight of 3.5±0.08 kg while the crosses obtained using Yankasa rams on Uda and Balami ewes gave the lowest birth weights (1.7±0.19 and 1.4±0.18, respectively). Sex and litter type have no significant effect (P>0.05) on gestation length. Birth weight was however affected by sex of lambs and their litter type. Litter type was negatively correlated with birth weight (-0.372). Gestation length had a low and non-significant relationship with birth weight; litter type and lamb genotype. Lamb genotype does not have a significant relationship with litter type. Genetic improvement of Nigeria sheep breed is possible if the resources of within and between breed is exploited. Selection for a reduction in gestation length may indirectly increase prolificacy. (Animal Production 12(3): 135-138 (2010)Key Words : gestation length, birth weight, Nigerian Sheep